Optimization of Sugar Palm Business Management to Increase Farmers' Income and Prosperity in Bukik Barisan Sub-District, Lima Puluh Kota Regency, West Sumatera Province - Sri Zulyanti Mardhiah, Asdi Agustar, Anwar Kasim, Mahdi (Universitas Andalas, 2017)
This paper aims to discuss how the actual potential of existing sugar palm development in farm households. The study was conducted using case study method, where the primary data is the main data used to address the research questions. Data were collection using questionnaire which were analysed with qualitative and quantitative approach. The result of the research shows that sugar palm is a commodity that has prospect to be developed to increase income and improve welfare of poor farmers. The potential of sugar palm business development was analysed in terms three aspects: 1) condition of land availability; 2) Manpower owned for palm sugar business; And 3) Experience about palm sugar plants business. Perceptions of farmers are also quite supportive for the development of palm sugarbusiness, although including the medium category because they look very open toaccept innovation.